Epidemiology, patterns of care and mortality for patients with hemodynamically unstable acute symptomatic pulmonary embolism - Jiménez, David; Bikdeli, Behnood; Barrios, Deisy; Quezada, Andrés; Del Toro, Jorge; Vidal, Gemma; Mahé, Isabelle; Quere, Isabelle; Loring, Mónica; Yusen, Roger D; Monreal, Manuel; Zdraveska M (Elsevier BV, 2018)
Limited information exists about the epidemiology, management and outcomes of hemodynamically unstable patients with acute pulmonary embolism (PE). We aimed to evaluate the prevalence and outcomes of unstable PE, and to assess the acute management in routine clinical practice.